(3OQQ GdCMcGe aj TQM ZQQ GdCMcGes - (3efdG NSQh, edG NSQh, eMeO Hf aQGeQR Hf Ydjs ((3efUhQ Hf TYHGf GdbGOQjs)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdMOhO, GdMO dZI(B: (3GdefY, hTQkYG(B: (3YbhHI ebOQI NQL Hg GdJYRjQEP dG JbOjQ ajg, hdjS dg bOQ eYjf aEf CcKQ JSYI hKdGKhf ShkWGs
(3BNQgG (B:s
(3BNQgG(B: (3GdhUj dh YRe Ydi JQc GdNUheI, cGf aSNgG HefRdI GdEbGdI, ajdRe GdhUj ceG dh JbGjdG MbjbI, aEPG aSN GdbGVj de jcf GbGdI adG jdRe GdhUj(B.s
(3jdjgG(B: (3eSGFd eajOI efJNHI ef cdGe GdCFeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 328s
(3cTa GdXfhf, L (B1: 747(3; (B2: 1199s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis